Pengaruh Kebijakan Stock Split Dan Right Issue Terhadap Harga Saham (studi pada perusahaan yang melakukan stock split dan right issue periode 2018-2020) Fidia Pangestika - Fidia Pangestika; Giyah Yuliari; C.H. Asta Nugraha; Siti Aminah (Serat Acitya, 2023)
This study aims to determine the influence of stock split policies (stock splits) and limited offer policies (right issue) on stock prices in companies listed on the Indonesia Stock Exchange (IDX). The stock price for a stock split is measured by the closing price and for the right issue using abnormal returns. The data used is the company's stock price data taken on the IDX and Yahoo Finance in 2018 to 2020. The population used in this study amounted to 52 companies consisting of 25 companies that conducted stock splits and 27 companies that conducted right issues and sampling using census methods or saturated samples. Hypothesis testing using wilcoxon signed rank test with observation period (event window) for stock split is 8 days and for the right issue which is 14 days, previously conducted normality test first using shapiro wilk test. The test results indicated that there was an influence on the stock split policy on the stock price in 2018 to 2020 with a significance value of 0.012. As for the right issue test, a significance value of 0.218 was obtained which means that there is no influence on the right issue policy on the stock price in 2018 to 2020.